Hukuman bagi Pelaku Tindak Pidana Pencabulan Pada Anak di Bawah Umur dan Perlindungan Korban - Cahaya Suratin; Erika Zakiyah; Muhammad Sholahudin Al Ayyubi; Virancya Indah Permatasari; Zulfi Hardiyanti Rochmah (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Abstract: Abuse often occurs in society. The majority of those who are victims of abuse are women and children. This article discusses the punishment for perpetrators of the criminal act of sexual abuse of minors. This research is normative juridical. The collected data is analyzed descriptively qualitatively. The study results concluded that the Criminal Act of Sexual Abuse against children is regulated in Law No. 23 of 2002 and Jo Law No. 35 of 2014 concerning Child Protection. What is meant by a child is a child who is not yet eighteen years old. Perpetrators of child abuse can be punished with a minimum imprisonment of 5 (five) years and a maximum of 15 (fifteen) years, and a maximum fine of Rp5,000,000,000.00 (five billion rupiahs)